BUDIDAYA IKAN AIR TAWAR DI LAHAN KERING DESA CAMPLONG II KECAMATAN FATULEU KABUPATEN KUPANG, NTT - Cynthia Dewi Gaina; Filphin Adolfin Amalo; Maxs. U. E. Sanam; Frans Umbu Datta; Inggrid Trinidad Maha; Yohanes T. R. M. R. Simarmata; Tri Utami (Jurnal Media Tropika, 2021)
Increasing the economy of rural communities is a process of improving an economic effort to meet the needs of life through an empowerment system form that meets human needs by utilizing surrounding natural resources. Natural resources owned by rural communities are the potential to be developed to improve the economy of the village community. If freshwater aquaculture is well developed and managed properly, it will bring beneficial results in line with the increase in fulfillment of public’ requirements. The purpose of community service program activities in Camplong II Village, Fatuleu District, Kupang Regency was community empowerment through freshwater aquaculture using the pond method. The people of Camplong II village have limited access to obtaining fresh fish products as its location is around 45-50 km from Kupang city which is known for its fresh sea products. Thus, the activities implemented were training on the installation of a square pond, providing 500 fish seeds and fish feed for 2 periods, mentoring and monitoring the maintenance of this pond, and developing human resources. The results obtained: installation of several fish pond with a diameter of 3 meters and a height of 4.0 m, an increase in community knowledge and skills, an early fish harvest stocked from this period which can improve the welfare of the community in Camplong II Village, Kupang Regency. From the results obtained there is potential in the form of land, water sources, and facilities that can be empowered to increase fish water farming production.